Knowledge and Experience in Creativity Techniques in Companies Metallurgic: A Diagnosis - Rodrigues, Jaqueline Fonseca; Eyng, Ivanilde Scussiatto; Lima, Isaura Alberton de; Teixeira, Enise Barth; Pilatti, Luiz Alberto (Revista ADMPG, 2010)
When emphasizing the division of activities longing to reach the desired objectives of the organization, emerges the increasing necessity to adopt new forms of management directed to the continuous processes of improvement of products and services. Ahead of this reality, the people who compose the enterprise will be made responsible in the taking of decisions. For the enterprise to have a sustainable growth, it is necessary that the involved individuals search through experience and knowledge, techniques based in creative capacity. The present work searched to diagnosis the level of knowledge and the level of experience of each technique of creativity in metallurgic industries, in Ponta Grossa - Paraná. In this direction the research is justified, since, the boarded topics in this work will serve of base so that other industries can stimulate the creative potential of their collaborators, creating surrounding that stimulate creativity. The methodology of field research that was used in this work estimates the diagnosis of the level of knowledge of the managers, as well as the diagnosis of the experience in the use of creativity techniques. The results of this research has perfectly shown to be possible to diagnosis how much the interviewed managers do not know, know or know well; they do not use, they use occasionally or they use creativity techniques regularly.